The principle of (dis)trust in the jurisprudential doctrine of the Supreme Court, regarding R.N. No. 1416-2018/Lima - Armendariz Ochoa, Luis (2025)
The purpose of this article is to critically examine the scope of the (dis)trust principle as a criterion for objective imputation within business organizational contexts. Within this framework, a normative review of this concept will be conducted from a functionalist perspective, emphasizing its differentiation and complementarity with the principle of trust, traditionally applied in criminal law. This paper will also address the arguments put forward by the Supreme Court in its ruling on Annulment Appeal No. 1416-2018, from the perspective of the proposed functionalist approach.